Spirochete antigens persist near cartilage after murine Lyme borreliosis therapy - Bockenstedt, Linda K. (American Society for Clinical Investigation, 2012)
An enigmatic feature of Lyme disease is the slow resolution of musculoskeletal symptoms that can continue after treatment, with some patients developing an inflammatory arthritis that becomes refractory to antibiotic therapy. Using intravital microscopy and the mouse model of Lyme borreliosis, we observed that Borrelia burgdorferi antigens, but not infectious spirochetes, can remain adjacent to cartilage for extended periods after antibiotic treatment. B. burgdorferi was not recovered by culture or xenodiagnosis with ticks after antibiotic treatment of WT mice and all but one of the immunodeficient mice with heightened pathogen burden due to impaired TLR responsiveness. Amorphous GFP(+) deposits were visualized by intravital microscopy in the entheses of antibiotic-treated mice infected with GFP-expressing spirochetes and on the ear cartilage surface in sites where immunofluorescence staining detected spirochete antigens. Naive mice were not infected by tissue transplants from antibiotic-treated mice even though transplants contained spirochete DNA. Tissue homogenates from antibiotic-treated mice induced IgG reactive with B. burgdorferi antigens after immunization of naive mice and stimulated TNF-α production from macrophages in vitro. This is the first direct demonstration that inflammatory B. burgdorferi components can persist near cartilaginous tissue after treatment for Lyme disease. We propose that these deposits could contribute to the development of antibiotic-refractory Lyme arthritis.